Demarkasi Semantik Siyādah dan Qawwāmah dalam Syawāhid Syair Arab - Rabi’atil Husni (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The interpretation of the meaning of qawwām in QS An-Nisā’ verse 34 is often reduced to the concept of absolute power, thus blurring the lexical distinction between the roots (Q-W-M) and (S-W-D) in classical Arabic. This study aims to reconstruct the lexical meaning of qawwām contextually through a philological-semantic study based on classical Arabic poetry as the main data source. The research data were collected through documentation techniques on eleven representative Arabic poetry stanzas from the Jahiliyah, Mukhadramūn, and early Islamic periods that contain the use of the roots (Q-W-M) and (S-W-D). Data analysis was carried out qualitatively with a philological-semantic approach, including the muqābalah technique to compare the meaning fields between lexemes, as well as morpho-syntactic analysis to identify grammatical functions and semantic relations in the context of poetry. The results of the study show three main findings. First, siyādah operates within the semantic field of prestige and static status, while qawwāmah represents operational actions related to work, physical fatigue, and the responsibility of protection. Second, the use of architectural metaphors such as qiwām al-bayt and arkān emphasizes the meaning of qawwām as a structural load-bearing, not a symbol of domination. Third, the poetic critique of the negligent figure of qayyim al-qawm shows that qawwāmah is functional and responsibility-based, not hierarchical-essential. This finding confirms that the diction of qawwāmūn in QS An-Nisā’ verse 34 lexically contains a mandate for active service and accountability, not the legitimacy of patriarchal supremacy.